2015
DOI: 10.1007/s13204-015-0406-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characterization of vacuum-deposited p-CdTe/n-ZnSe heterojunctions

Abstract: In this paper, we report a heterojunction of p-CdTe/n-ZnSe fabricated on a quartz substrate using thermal evaporation technique. The materials have a larger band gap difference in comparison to other II-VI heterojunctions-involving CdTe. The larger band gap difference is expected to increase diffusion potential and photovoltaic conversion efficiency. The electrical conduction mechanism involved, barrier height and band offset at the interface that are crucial to determine device performance are evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The suitability of CdS thin film as a good window layer material capable of providing excellent receptive surface to absorber layer materials such as p-type cadmium telluride (CdTe), p-type copper indium selenide (CuInSe2), etc is owned to its high electron affinity [3]. Despite the potential of CdS in the formation of heterojunction based solar cells, there is need to treat its surface for better receptive surface which offer better improvement on the electrical parameters of the photovoltaic solar cells [4][5][6]. CdTe thin film as one of the primary candidates in the field of photovoltaic technology has gained worldwide prominence owning to its near ideal bandgap energy of 1.45 eV for the absorption of photons [6].…”
Section: Introductionmentioning
confidence: 99%
“…The suitability of CdS thin film as a good window layer material capable of providing excellent receptive surface to absorber layer materials such as p-type cadmium telluride (CdTe), p-type copper indium selenide (CuInSe2), etc is owned to its high electron affinity [3]. Despite the potential of CdS in the formation of heterojunction based solar cells, there is need to treat its surface for better receptive surface which offer better improvement on the electrical parameters of the photovoltaic solar cells [4][5][6]. CdTe thin film as one of the primary candidates in the field of photovoltaic technology has gained worldwide prominence owning to its near ideal bandgap energy of 1.45 eV for the absorption of photons [6].…”
Section: Introductionmentioning
confidence: 99%
“…Precisely measuring critical current density in superconducting materials and systems requires understanding of the fundamentals of current-voltage (IV) characteristics, also called the transport measurements [1]. Recent studies have shown that these IV curves may show sudden jumps, which resemble Shapiro steps, in voltage around critical current (I c ) and/or critical temperature (T c ) in superconducting thin films.…”
Section: Introductionmentioning
confidence: 99%